THE IMPORTANCE OF INTEGRATIVE AND AXIOLOGICAL APPROACHES IN DEVELOPING PROFESSIONAL MOBILITY (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the pedagogical potential, theoretical-methodological foundations, and practical significance of integrative and axiological approaches in developing professional mobility among university students. The study examines the structural components of professional mobility, its importance in the modern educational environment, and the role of interdisciplinary integration and value-oriented education in the formation of professional competence among future specialists. Furthermore, it substantiates that the harmonious implementation of integrative and axiological approaches positively influences students’ adaptability, creativity, reflective activity, and professional self-development competencies. The research findings indicate that these approaches create favorable conditions for preparing professionally mobile, competitive, and innovative specialists capable of effective performance in rapidly changing professional environments.